Surgical Reconstruction Using a Flanged Mesh Cage without Plating for Cervical Spondylotic Myelopathy and a Symptomatic Ossified Posterior Longitudinal Ligament - Kang, Jung Hoon (J Korean Neurosurg Soc, 2019)
OBJECTIVE: We introduce innovative method of cervical column reconstruction and performed the reconstruction with a flanged titanium mesh cage (TMC) instead of a plate after anterior corpectomy for cervical spondylotic myelopathy (CSM) and an ossified posterior longitudinal ligament (OPLL). METHODS: Fifty patients with CSM or OPLL who underwent anterior cervical reconstruction with a flanged TMC were investigated retrospectively. Odom’s criteria were used to assess the clinical outcomes. The radiographic evaluation included TMC subsidence, fusion status, and interbody height. Thirty-eight patients underwent single-level and 12 patients underwent two-level corpectomy with a mean follow-up period of 16.8 months. RESULTS: In all, 19 patients (38%) had excellent outcomes and 25 patients (50%) had good outcomes. Two patients (4%) in whom C5 palsy occurred were categorized as poor. The fusion rate at the last follow-up was 98%, and the severe subsidence rate was 34%. No differences in subsidence were observed among Odom’s criteria or between the single-level and two-level corpectomy groups. CONCLUSION: The satisfactory outcomes in this study indicate that the flanged TMC is an effective graft for cervical reconstruction.